Effects of Spray-Dried Lactococcus-Based Fermentation Products on Growth Performance of Nursery Pigs - K. M. Dunmire; M. B. Braun; G. E. Nichols; C. E. Evans; M. Saensukjaroenphon; C. N. Truelock; J. C. Woodworth; J. Callura; C. B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2019)
A total of 720 barrows (initially 13.0 lb; Line 200 × 400; DNA, Columbus, NE) from 2 study groups (360 pigs per study group), were used in a 42-d growth trial to test the effects of spray-driedLactococcus-based fermentation products on nursery pig performance. There were 24 replications per treatment and 5 pigs per pen. For both experiments, pens of pigs were randomly allotted to 1 of 6 dietary treatments in a completely randomized design. There were six treatment diets fed in 3 phases. The positive control diet included zinc oxide (phase 1), zinc oxide + chlortetracycline (CTC; phase 2) while the negative control diet did not include zinc oxide or CTC. Treatment diets included the negative control + 1 of 4 fermentation products (C, D, E, or F) added at 5% of the diet. Phase 3 diets contained a common control diet fed to all pigs plus treatment diets (C, D, E, and F). Phase 1 and 2 diets were fed in pelleted form and phase 3 in mash form. From d 0 to 20, there was an overall treatment effect (P= 0.001) where pigs fed the positive control had increased (P<0.05) d 20 weight, average daily gain (ADG), average daily intake (ADFI), and improved feed efficiency (F/G) compared to those fed the negative control and negative control + fermentation product. From d 20 to 42, there was an overall treatment effect (P= 0.003) for F/G where pigs fed the negative control had improved (P<0.05) F/G compared to those fed additive D, E, and F. Overall, there was a treatment effect (P= 0.03) for pigs fed the positive control having improved (P<0.05) ADG and F/G compared to the negative control and negative control + fermentation product. In addition, pigs fed the negative control had improved (P<0.05) F/G compared to those fed additive D, E, and F. In conclusion, pigs fed the positive control (zinc + CTC) diet had improved performance compared to pigs fed the negative control with or without fermentation product.
Keywords: fermentation product; nursery pigs; pellet quality